Exploiting mesoporous silica nanoparticles as versatile drug carriers for several routes of administration - Sábio, Rafael Miguel [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Martins dos Santos, Aline [UNESP]; Monteiro, Andreia Sofia [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2021)
The exploitation of mesoporous silica nanoparticles (MSNs) as drug delivery systems has grown exponentially due to their remarkable tunable properties, such as high surface area, chemical and physical stability, high loading and release capacities, distinct possibilities of particle and pore structures, as well as good biocompatibility, biodegradability, and easy clearance. However, the main exposure routes that exploit MSNs qualities, namely intravenous, subcutaneous, intramuscular, intratumoral, ophthalmic, pulmonary, nasal, dermal, and oral administrations, have been underreported to date. In addition, a better understanding of these administration routes can contribute to the development of smart MSNs-based nanoplatforms with interesting properties, such as high stability in physiological media, specificity and efficacy in theranostic applications, and further clinical translations. This review highlights the advantages and challenges of the administration routes aforementioned regarding the MSNs as drug delivery systems. It also shows how their properties can influence the interaction with biological media, and consequently, their biocompatibility, biodistribution, and clearance mostly in pre-clinical assays, in order to contribute to further MSNs-based nanoplatform clinical translations.
Keywords: Administration routes; Biological behavior; Drug delivery systems; Mesoporous silica nanoparticles (MSNs)